(untitled) (ARQUISUR Revista, 2015)
This research studies the evolution of emergency housing since the beginning of twentieth century to the present. The list of cases on examination, does not pretend to follow strictly the chronology of the century, it is intentionally structured proceeding from the simple to the complex. It starts with the minimum dwelling of modern architecture, based on the faith in technology. However, the cases will gradually turn more social concerned. This should not be seen as an opposition between technology and social concerning. On the contrary, this research discusses how social demands enhance and promote new technical solutions. Even when some technological requirements remain all along the century, as the attempt to create practical and massive solutions for instance, social concerning tend to grow. The selection of cases center the attention in some celebrated characters of Architecture History, beginning with the pioneers of modern architecture moving towards Latin American context. More than a geographical perspective, it is pretended to achieve a wide cultural view. It shifts from the stable paradigm of industry to the chaotic context of Latin American cities during the post–industrial age.